2013
DOI: 10.1093/ajh/hpt176
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Effects of Concord Grape Juice on Endothelial Function and Arterial Stiffness in Healthy Smokers

Abstract: CGJ consumption improved endothelial function and vascular elastic properties of the arterial tree in healthy smokers and attenuated acute smoking-induced impairment of arterial wall properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 35 publications
1
66
0
2
Order By: Relevance
“…Dohadwala et al [44] demonstrated that concentrated cranberry juice (480 ml/ d) significantly improved carotid-femoral PWV after 6 weeks of supplementation in patients with CAD. This is supported by another study in apparently healthy smokers, which showed a significant improvement in PWV after only 2 weeks of supplementation with polyphenols-rich Concord grape juice [39] compared with low polyphenol-rich juice. This intervention also attenuated a post-cigarette deterioration in PWV at 7 days and 2 weeks.…”
Section: Fruit and Vegetables And Vascular Functionsupporting
confidence: 56%
See 1 more Smart Citation
“…Dohadwala et al [44] demonstrated that concentrated cranberry juice (480 ml/ d) significantly improved carotid-femoral PWV after 6 weeks of supplementation in patients with CAD. This is supported by another study in apparently healthy smokers, which showed a significant improvement in PWV after only 2 weeks of supplementation with polyphenols-rich Concord grape juice [39] compared with low polyphenol-rich juice. This intervention also attenuated a post-cigarette deterioration in PWV at 7 days and 2 weeks.…”
Section: Fruit and Vegetables And Vascular Functionsupporting
confidence: 56%
“…Conversely, another study showed no effect on FMD after 7 days of supplementation with tomato puree (70 g/d) in postmenopausal, healthy women compared with placebo [37]. Fruit and vegetable supplement capsules have been shown to attenuate the FMD reduction in response to a high fat meal compared with placebo capsules [38] while a recent study demonstrated polyphenols-rich juice from Concord grapes significantly improved FMD compared with polyphenols-poor juice and prevented a postcigarette reduction in FMD after only 7 days, suggesting polyphenols are important in determining endothelial function [39]. Encapsulated grape solids (6Â 500 mg/d for two weeks) had no effect on FMD response to a high fat meal [40].…”
Section: Fruit and Vegetables And Endothelial Vasodilator Functionmentioning
confidence: 99%
“…It was suggested that the oriental plum fruit juice concentrate could exert a significant cardiovascular protective effect [89]. Moreover, endothelial function and arterial tree vascular elastic properties could be improved by consuming Concord grape juice [90]. …”
Section: Mechanisms Of Action Of Juice On Cardiovascular Diseasesmentioning
confidence: 99%
“…Despite promising initial results, however, alagebrium has not been studied in phase III trials, perhaps related to a number of negative results in other therapeutic areas [99][100][101][102][103]. A number of nutritional supplements such as flavonoids [104,105], isoflavone [106], omega-3 [106] and tetrahydrobiopterin [107,108] acting via an antioxidant effect and/or improvement of NO bioavailability have also been shown to improve arterial stiffness. However, these studies have similar limitations as discussed above [106].…”
Section: Origins Of Arterial Stiffness and Nurture Versus Nature?mentioning
confidence: 99%